Pengaruh Profitabilitas, Likuiditas, dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Sub Sektor Makanan dan Minuman - Ulfa, Meliyana; Effendy, Lukman (Jurnal Riset Mahasiswa Akuntansi, 2025)
In recent years, the company value within Indonesia’s food and beverage sub-sector has shown noticeable fluctuations, especially in the aftermath of the COVID-19 pandemic. This volatility presents an interesting area of study, as company value reflects how investors perceive a firm’s performance and future prospects. This research aims to examine the influence of profitability, liquidity, and firm size on company value, focusing on food and beverage companies listed on the Indonesia Stock Exchange during the 2020– 2023 period. Using a quantitative approach with multiple linear regression analysis, the study finds that profitability and firm size have a positive and significant impact on company value. In contrast, liquidity has a significant negative effect. These findings suggest that efficient financial management and an optimal business scale play an important role in enhancing investor confidence and, consequently, company value.